Chemical Synthesis and Antitumor Evaluation of Chikusetsusaponin IVa Butyl Ester and Its Analogues - Zheng, Jibin; Wang, Yanxiao; Zhang, Yiyue; Rong, Jingjing; He, Dongjuan; Wang, Xiaotong; Zhang, Liangliang; Xu, Jianguang; Cao, Peng; Yang, You (Synlett, 2024)
Chikusetsusaponin IVa butyl ester (CS-IVa-Be) is a triterpene saponin that acts as a novel IL6R antagonist for inducing breast cancer cell apoptosis. However, the structure–activity relationship for this class of saponins remains unclear. Here, we report a gram-scale synthesis of CS-IVa-Be and the efficient preparation of eight of its analogues. CS-IVa-Be was demonstrated to have significant antitumor activities against MDA-MB-231, HepG2, and A549 cells. When one of the sugar residues at either the 3-OH or 28-COOH position of CS-IVa-Be was cleaved, or the length of the alkyl chain on the d-glucuronic acid residue of CS-IVa-Be was changed, these analogues showed varied inhibitory activities against the cancer cell lines. Notably, the carboxylic acid form of CS-IVa-Be exhibited a stronger antitumor activity against MDA-MB-231 cells. Furthermore, the carboxylic acid form of CS-IVa-Be inhibited MDA-MB-231 cell proliferation in a dose-dependent manner by arresting the cell cycle at the G2/M phase.
Keywords: glycosides; glycosylation; carbohydrates; natural products; medicinal chemistry